2021
DOI: 10.3390/jcm10122548
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Disease and Anti-Myeloperoxidase Antibodies: Not a Simple Association

Abstract: Anti-neutrophil cytoplasmic antibodies (ANCA), mainly anti-myeloperoxidase (MPO) antibodies, have been frequently identified in patients with idiopathic pulmonary fibrosis (IPF). However, their role remains unclear, and only 7–23% of these patients develops clinically overt vasculitis. We aimed to investigate the clinical, serological, and radiological features and prognosis of anti-MPO-positive interstitial lung disease (ILD) patients. Fifty-eight consecutive patients firstly referred for idiopathic interstit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…Previous studies have shown that MPO-ANCA and MPA have the strongest association with ILD. 5 7 In clinical practice, ILD patients with ANCA positivity and extrapulmonary involvement meet the AAV diagnostic criteria and receive a diagnosis of AAV-ILD, but some ILD patients present with isolated ANCA positivity without manifestations of extrapulmonary systemic vasculitis. This group of patients can be initially diagnosed with idiopathic pulmonary fibrosis (IPF), IIP or IPAF before systemic vasculitis manifestations occur in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that MPO-ANCA and MPA have the strongest association with ILD. 5 7 In clinical practice, ILD patients with ANCA positivity and extrapulmonary involvement meet the AAV diagnostic criteria and receive a diagnosis of AAV-ILD, but some ILD patients present with isolated ANCA positivity without manifestations of extrapulmonary systemic vasculitis. This group of patients can be initially diagnosed with idiopathic pulmonary fibrosis (IPF), IIP or IPAF before systemic vasculitis manifestations occur in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…In Other authors reported the presence of ANCA in patients with IPF, with a prevalence up to 35% in the Japanese population (28)(29)(30). However, the occurrence of vasculitis, mainly MPA, has been described in a minority of these cases and only 7-23% of ANCA-positive subjects with a diagnosis of IPF subsequently developed a clinically overt vasculitis, mainly in patients with anti-MPO antibodies (28,29).…”
Section: Discussionmentioning
confidence: 98%
“…ANCA themselves seem related to the development of ILD, even without concomitant vasculitis: several papers have reported a significant variable percentage of ANCA-positive patients with ILD but with no extra-pulmonary signs or symptoms of AAV [ 24 ].…”
Section: Discussionmentioning
confidence: 99%